A learner-centred design of a location-aware learning reminder. (31st July 2008) - Ryu, Hokyoung; Parsons, David
To ensure the success of future mobile learning environments, it is essential to develop affordable and effective applications that are well matched to the characteristics of the users' (particularly, learners) learning experiences. As an early exploration of this line of study, this paper evaluates a location-aware learning organiser that can help university students to manage their learning activities through mobile devices. Empirical testing of the learning organiser revealed considerable benefits for students in the university context, and demonstrated some potential opportunities for them to be more engaged in further mobile learning activities.